Desain Dan Implementasi Program Mentoring Berbasis Kecerdasan Emosional Untuk Pengembangan Profesional Dosen Muda - Imamah, Istianatul; Aimah, Siti (LP2M Universitas Islam Ahmad Dahlan, 2025)
This study examines the effectiveness of an emotional intelligence-based mentoring program in developing teaching skills, collaboration, and academic careers of young lecturers at KH. Mukhtar Syafaat University, Banyuwangi. Using a qualitative case study approach, data were collected through observation, interviews, and documentation. Data analysis involved data reduction, presentation, and conclusion drawing, with triangulation for validity. The findings show that the emotional intelligence-based mentoring program effectively supports the professional growth of young lecturers. The program focuses on empathy, self-awareness, and social skills, which enhance teaching, academic communication, and adaptation to institutional dynamics. Positive mentor-mentee interactions foster an environment conducive to personal and professional development. Additionally, the program successfully cultivated a culture of mutual support through continuous mentoring, including collaborations in author programs, research, Community Service (PKM), and Lecturer Performance Reports (LKD). However, challenges such as time limitations and generational experience gaps persist, offering valuable feedback for future improvements to the program.